POLYNOMIAL(PLS ANSWER FAST)

Asked by prakharsrivastava | 1st May, 2010, 08:40: AM

Expert Answer:

By division theorem of Algorithm, we know that

p(x) = q(x).g(x) + r(x)

3x3+x2+2x+5 = (3x- 5).g(x) + 9x + 10

3x3+x2 - 7x - 5 = (3x-5).g(x)

So, g(x) = (3x3+x2 - 7x - 5)/ (3x - 5)

               = x2 + 2x + 1

For the second question, substitute x  = -1 in the polynomial P(x)=3x3-5x2-11x-3 as it is given that -1 is the zero of the polynomial. The polynomial will reduce down to a quadratic polynomial. Equate it to zero and factorise to get the remaining two zeroes.

Answered by  | 3rd May, 2010, 09:41: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.